Borg vs. McEnroe [videorecording (DVD)] - Sverrir Gudnason, 1978-; LaBeouf, Shia, 1986-; Skarsgård, Stellan (Virgil Films, 2018)
Wimbledon, 1980. The rainiest summer in decades. The world is waiting to see the number one tennis player in the world, Bjorn Borg, claim his fifth Wimbledon title. But few know of the drama behind the scenes: at only 24, Borg is close to the end, run-down, worn out and ridden with anxiety. Meanwhile, the challenger John McEnroe, 20, has decided to replace his former hero on the Wimbledon throne. A story about the price of success.